Handbook of Heterogeneous Catalysis 2008
DOI: 10.1002/9783527610044.hetcat0116
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Distillation

Abstract: The sections in this article are Introduction Potential versus Constraints Practical Realization of Catalytic Distillation Tray Towers Packed Towers Modeling Catalytic Distillation Equilibrium‐Stage Models Rate‐Based Models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Theoretically, the cutting temperature can be presumed by referring to the normal boiling points and distribution of sulfides. However, the true boiling points of sulfides obtained in true boiling point distillation experiments are usually much lower than the normal boiling points of some sulfides, because sulfides and aliphatic and aromatic hydrocarbons in FCC naphtha can form azeotropes, whose boiling points are significantly lower than the corresponding sulfides. Therefore, determining the cutting temperature according to the normal boiling points of sulfides is not reliable for real FCC naphtha, leading to the difficulty in designing and operating FCC naphtha hydrotreating processes. To the best of our knowledge, it seems that the only result regarding the prediction of the cutting temperature between LCN and HCN is that due to Liang et al Observing that the distributions of olefins and sulfides in the narrow cuts of FCC naphthas are similar, they indicated that an optimum cutting temperature for producing Euro IV standard petrol should be in the range of 72–80 °C, at which the majority of C 7 -olefins could enter into the resultant LCN.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the cutting temperature can be presumed by referring to the normal boiling points and distribution of sulfides. However, the true boiling points of sulfides obtained in true boiling point distillation experiments are usually much lower than the normal boiling points of some sulfides, because sulfides and aliphatic and aromatic hydrocarbons in FCC naphtha can form azeotropes, whose boiling points are significantly lower than the corresponding sulfides. Therefore, determining the cutting temperature according to the normal boiling points of sulfides is not reliable for real FCC naphtha, leading to the difficulty in designing and operating FCC naphtha hydrotreating processes. To the best of our knowledge, it seems that the only result regarding the prediction of the cutting temperature between LCN and HCN is that due to Liang et al Observing that the distributions of olefins and sulfides in the narrow cuts of FCC naphthas are similar, they indicated that an optimum cutting temperature for producing Euro IV standard petrol should be in the range of 72–80 °C, at which the majority of C 7 -olefins could enter into the resultant LCN.…”
Section: Introductionmentioning
confidence: 99%